PLGA Nanoparticle-Peptide Conjugate Effectively Targets Intercellular Cell-Adhesion Molecule-1 - Zhang, Na (2007)
Targeted delivery of therapeutics possesses the potential to localize therapeutic agents to a specific tissue as a mechanism to enhance treatment efficacy and abrogate side effects. Antibodies have been used clinically as therapeutic agents and are currently being explored for targeting drug-loaded nanoparticles. Peptides such as RGD peptides are also being developed as an inexpensive and stable alternative to antibodies. In this study, cyclo(1,12)PenITDGEATDSGC (cLABL) peptide was used to target nanoparticles to human umbilical cord vascular endothelial cells (HUVEC) monolayers that have upregulated intercellular cell-adhesion molecule-1 (ICAM-1) expression. The cLABL peptide has been previously demonstrated to possess high avidity for ICAM-1 receptors on the cell surface. Poly(DL-lactic-co-glycolic acid) nanoparticles conjugated with polyethylene glycol and cLABL demonstrated rapid binding to HUVEC with upregulated ICAM-1, which was induced by treating cells with the proinflammatory cytokine, interferon-γ. Binding of the nanoparticles could be efficiently blocked by pre-incubating cells with free peptide suggesting that the binding of the nanoparticles is specifically mediated by surface peptide binding to ICAM-1 on HUVEC. The targeted nanoparticles were rapidly endocytosed and trafficked to lysosomes to a greater extent than the untargeted PLGA-PEG nanoparticles. Verification of peptide-mediated nanoparticle targeting to ICAM-1 may ultimately lead to targeting therapeutic agents to inflammatory sites expressing upregulated ICAM-1.